Immunological interactions between Piscine orthoreovirus and Salmonid alphavirus infections in Atlantic salmon. Issue 64 (May 2017) - Røsæg, Magnus Vikan; Lund, Morten; Nyman, Ingvild Berg; Markussen, Turhan; Aspehaug, Vidar; Sindre, Hilde; Dahle, Maria Krudtaa; Rimstad, Espen
Abstract: Heart and skeletal muscle inflammation (HSMI) and pancreas disease (PD) cause substantial losses in Atlantic salmon ( Salmo salar ) aquaculture. The respective causative agents, Piscine orthoreovirus (PRV) and Salmonid alphavirus (SAV), are widespread and often concurrently present in farmed salmon. An experimental infection in Atlantic salmon was conducted to study the interaction between the two viruses, including the immunological mechanisms involved. The co-infected fish were infected with PRV four or ten weeks before they were infected with SAV. The SAV RNA level and the PD specific lesions were significantly lower in co-infected groups compared to the group infected by only SAV. The expression profiles of a panel of innate antiviral response genes and the plasma SAV neutralization titers were examined. The innate antiviral response genes were in general upregulated for at least ten weeks after the primary PRV infection. Plasma from co-infected fish had lower SAV neutralizing titers compared to the controls infected with only SAV. Plasma from some individuals infected with only PRV neutralized SAV, but heat treatment removed this effect. Field studies of co-infected fish populations indicated a negative correlation between the two viruses in randomly sampled apparently healthy fish, in line with the experimental findings, but a positive correlation in moribund or dead fish. The results indicate that the innate antiviral response induced by PRV may temporary protect against a secondary SAV infection. Highlights: Piscine orthoreovirus (PRV) and Salmonid alphavirus (SAV) are often concurrently present in farmed Atlantic salmon. The SAV level and the PD specific lesions were significantly lower in co-infected groups. The innate antiviral response genes were upregulated for at least ten weeks after the primary PRV infection. Field studies indicated a negative correlation between the two viruses in randomly sampled apparently healthy fish. The innate antiviral response induced by PRV may temporary protect against a secondary SAV infection.